Thermal expansion of organic superconductor κ-(D₄-BEDT-TTF)₂Cu{N(CN)₂}Br. Isotopic effect - Dolbin, A.V.; Khlistuck, M.V.; Eselson, V.B.; Gavrilko, V.G.; Vinnikov, N.A.; Basnukaeva, R.M.; Konstantinov, V.A.; Nakazawa, Y. (Физика низких температур, 2017)
Linear thermal expansion coefficient (LTEC) of single crystal κ-(D₄-BEDT-TTF)₂Cu[N(CN)₂]Br was studied across the crystal layers in the temperature range 2–290 K using the method of precise capacitive dilatometry. Below Tc = 11.6 K the LTEC of the sample had a small negative value, which is apparently due to the transition from the paramagnetic metal in the superconducting state. There was a bend of temperature dependence of the LTEC, which shows broad peak around 40 K and can be attributed to the elastic lattice anomaly around the end-point of Mott boundary. A sharp jump in the LTEC values and hysteresis was observed in the area of Tg ∼ 75–77 K, what is likely explained by the transition in a glass-like state. The isotope effect in the thermal expansion is discusses, which manifested itself in a shift of the phase transitions in comparison with fully deuterated BEDT-TTF sample.